(untitled) (International Journal of Contemporary Security Studies, 2022)
In this paper is analyzed mobbing behavior as a new and complex phenomenon for domestic legislation and jurisprudence in the Republic of Serbia. Despite the fact that there is a great number of definitions of maltreatment at workplaces, all of them are based on making hostile, humiliating and degrading environment at work. Since the serbian Act on Prevention of Harassment at Work is adopted in 2010, judicial protection for employees is provided not only in criminal procedure in line with the rules of Criminal Code and the Code of Criminal Procedure but also ih the civil trial. Proving mobbing behaviour in civil trial is different from criminal procedure regarding the turnover of the burden of proof, different kinds of admissible evidence and the rule of repetition of behavior which is considered to be mobbing. Altough the Act on Prevention of Harassment at Work is in force during ten years, we have not found precise criteria in the jurisprudence for remarking the hrassment at work and it is one of the reasons why appellate courts intervene in the decisions of higher courts regarding the mobbing behavior.